SUMBER STRES DALAM ORGANISASI PENDIDIKAN - Fika Handini; Raudatun; Andaffa Favian Nugraha; Yudo Handoko (STKIP Subang, 2026)
Occupational stress in educational organizations has become a significant issue due to the increasing demands of education, administrative workloads, technological changes, and professional responsibilities faced by educators and educational staff. This study aims to analyze the sources, causes, impacts, and stress management strategies in educational organizations. The study used a qualitative approach with a literature review method, examining relevant journals, books, and academic articles. Data were collected through documentary studies and analyzed using descriptive qualitative analysis. The results indicate that the main sources of stress include excessive workload, time pressure, policy changes, limited facilities, technological adaptation, and organizational conditions. Occupational stress affects emotional stability, physical health, productivity, and organizational effectiveness. The study also found that a supportive work environment, effective communication, a balanced workload, and psychological well-being programs such as the PERMA approach can help reduce stress and burnout among educators and educational staff. Therefore, stress management is crucial for improving the quality of educational services and human resources in educational institutions.